Radiology of COVID-19 pneumonia - Said-Hartley, Qonita; Moosa, Sulaiman (SA Heart Journal, 2020)
Coronavirus disease (COVID-19) started as a cluster of pneumonia cases in December 2019 and has rapidly spread across the world, resulting in millions of infections, and approaching one million deaths. In this short review we describe the most common chest x-ray and computed tomography manifestations of the virus as it affects the respiratory system, and make brief references to the common clinical presentations.